2021
DOI: 10.1123/ijspp.2020-0675
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Characteristics of Elite Youth Athletes: A Clustering Approach to Optimize Sleep Support Strategies

Abstract: Purpose: Elite athletes experience chronic sleep insufficiency due to training and competition schedules. However, there is little research on sleep and caffeine use of elite youth athletes and a need for a more nuanced understanding of their sleep difficulties. This study aimed to (1) examine the differences in sleep characteristics of elite youth athletes by individual and team sports, (2) study the associations between behavioral risk factors associated with obstructive sleep apnea and caffeine use with sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
3
6
0
2
Order By: Relevance
“…Many of these sports traditionally include early-morning training and high training volumes and durations, whereas many of the individual sports in the current study might not necessarily be associated with early or late-night training (e.g., badminton, golf, and tennis). Conversely, our results are in agreement with the findings of Suppiah et al (2021) 21 , who observed better sleep characteristics in elite individual-sport youth athletes compared to those in team-sports. Indeed, the individual sport cohort in the Suppiah et al 21 study also included many non-endurance based individual athletes.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Many of these sports traditionally include early-morning training and high training volumes and durations, whereas many of the individual sports in the current study might not necessarily be associated with early or late-night training (e.g., badminton, golf, and tennis). Conversely, our results are in agreement with the findings of Suppiah et al (2021) 21 , who observed better sleep characteristics in elite individual-sport youth athletes compared to those in team-sports. Indeed, the individual sport cohort in the Suppiah et al 21 study also included many non-endurance based individual athletes.…”
Section: Discussionsupporting
confidence: 94%
“…Conversely, our results are in agreement with the findings of Suppiah et al (2021) 21 , who observed better sleep characteristics in elite individual-sport youth athletes compared to those in team-sports. Indeed, the individual sport cohort in the Suppiah et al 21 study also included many non-endurance based individual athletes. The inconsistencies in athlete sleep characteristics by sport type between studies highlights that contextual between-sport differences may exist.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Junior (<18 years of age) athletes often receive less sleep than these recommendations (Riederer, 2020). Sleep quality has also been shown to be impaired in junior athletes (Suppiah et al, 2021). Sleep duration and sleep quality may be impaired by lifestyle factors, including school commencement times, homework, and potential social media and gaming (Hansen et al, 2017;Wahlstrom et al, 2017).…”
Section: Introductionmentioning
confidence: 99%